Convergence theorems for G-Nonexpansive mappings in CAT(0) spaces endowed with graphs - Watcharapong Anakkamatee (2020)
© 2019 by the Mathematical Association of Thailand. In this paper, we introduce the concept of a CAT(0) space endowed with a graph. Browder’s convergence theorem and Halpern iteration process for G-nonexpansive mappings in an underlying space will be presented. This result extends and generalizes the result of Tiammee, Kaewkhao and Suantai (2015).